2010
DOI: 10.1186/1478-811x-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry and intracellular fate of TRIM-containing TCR complexes

Abstract: BackgroundStudying the stoichiometry and intracellular trafficking of the T cell antigen receptor (TCR) is pivotal in understanding its mechanisms of activation. The αβTCR includes the antigen-binding TCRαβ heterodimer as well as the signal transducing CD3εγ, CD3εδ and ζ2 subunits. Although the TCR-interacting molecule (TRIM) is also part of the αβTCR complex, it has not been included in most reports so far.ResultsWe used the native antibody-based mobility shift (NAMOS) assay in a first dimension (1D) blue nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Importantly, previous work has demonstrated that the expression of a mutated recycling defect ␤2 integrin is directed into the late endosome compartment (67). In addition, recent work has proposed differential endosomal trafficking for members of the TCR/CD3 complex (68,69), and yet the mechanisms behind this trafficking remain unclear. Our data suggest that WASH may be a key regulator of TCR/CD3 complex trafficking in activated T cells and of LFA-1 in either the naive or activated state and that WASH is involved in efficient recycling of these receptors back to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, previous work has demonstrated that the expression of a mutated recycling defect ␤2 integrin is directed into the late endosome compartment (67). In addition, recent work has proposed differential endosomal trafficking for members of the TCR/CD3 complex (68,69), and yet the mechanisms behind this trafficking remain unclear. Our data suggest that WASH may be a key regulator of TCR/CD3 complex trafficking in activated T cells and of LFA-1 in either the naive or activated state and that WASH is involved in efficient recycling of these receptors back to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus on the composition of the TCR complex is that it is comprised of TCRαβ, CD3γε, CD3δε, and CD3ζ 2 dimers. In addition, some TCRs include a dimer of the TM protein TRIM . Therefore, the minimal stoichiometry possible is αβγεδεζζ.…”
Section: The Stoichiometry Of the Tcr Remains Unresolvedmentioning
confidence: 99%
“…It consists of the antigen-recognizing TCR␣␤ (or TCR␥␦) heterodimer and the signal-transducing CD3 dimers: CD3⑀␥, CD3⑀␦, and (1, 2). The basic functional unit of the TCR, defined as the monomeric TCR, has a TCR␣␤CD3␦⑀␥⑀ stoichiometry (3)(4)(5)(6).…”
mentioning
confidence: 99%